Determinants of Attitude Toward Political Parties in Palestine: The effect of the Egyptian Revolution on supporters of Fatah and Hamas - Hamanaka, Shingo (Asian Journal for Public Opinion Research, 2013)
For the Palestinians, what is the impact of the Arab Spring? The revolution not only dislodged Mubarak from the presidency, but also changed Egyptian policy regarding Palestinians in Gaza. New Egyptian diplomacy has encouraged Hamas and Fatah, which had been in dispute, to seek reconciliation and has loosened the border control on humanitarian grounds. We focus on Palestinian voting attitudes in the wake of the Arab Spring. Despite the vast quantity of literature written about Palestinian politics since the first decade of the millennium, we know little about the determinants of Palestinian attitudes toward the divided governments in the West Bank and the Gaza Strip. The Fatah government, in the West Bank, increased in popularity after submitting a request for UN recognition of Palestinian statehood. In Gaza, the Hamas government lost popularity because of mismanagement but won support through the success of its prisoner swap deal with Israel. However, evaluation of the ruling party does not depend only on one-time events. This research attempts to measure the impact of policy change in Gaza after the Arab Spring. We provide an account of our research on Palestinian attitudes toward the divided governments based on two sets of the original survey data conducted in May 2009 and June 2012. The paper sheds light on Palestinian attitudes and makes clear the effects of "democratization" in the Middle East and the effects of regional context factors on the occupied Palestinians.